ETUDES HELMINTHOLOGIQUES SUR LA VALLEE DE RIO PAPALOAPAN MEXIQUE II QUELQUES FILAIRES DE BATRACIENS ET DOISEAUX - CABALLERO Y C, EDUARDO; C (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
The proteolytic activity of latex mexicain from P mexicanus increases with the development of the fruits, reach- ing a max before their ripening This proteolytic activity, given in milliequiv of tyrosine freed in 15 min of digestion by 1 mg of prote
ANN PHYS N Y
Keywords: ETUDES, HELMINTHO LOGIQUES, VALLEE DE RIO PAPALOAPAN, MEXIQUE , QUELQUES FILAIRES, BATRACIENS, DOISEAUX; CIENCIAS DE LA VIDA; MICROBIOLOGIA; BACTERIOLOGIA